Analisis Strategi Komunikasi Politik Puan Maharani sebagai Ketua Dewan Perwakilan Rakyat dalam Merespons Kritik Publik pada Pemberitaan di MediaIndonesia.com - Roisatunnisa, Roisatunnisa; Ahmad Miftah Rizky; Muhammad Shohibul Izar; Niken Wulandari (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This study examines Puan Maharani’s political communication strategy as Speaker of the Indonesian House of Representatives in responding to public criticism reported by MediaIndonesia.com. Using a constructivist paradigm, a qualitative descriptive approach, and Aristotelian rhetorical theory (ethos, pathos, and logos), the study analyzes news texts containing her statements. The findings show that Puan employs a reflective and legitimative rhetoric by acknowledging criticism, using inclusive emotional language, and presenting rational arguments. This strategy aims to rebuild public trust and strengthen the DPR’s institutional image in the digital media era.